An exploration into the impact of patient aggression towards staff in secure forensic hospitals – from risk factors to coping - Allen, Rachel (2019)
The aim of this thesis was to develop better understanding of the role of inpatient aggression in forensic healthcare settings. This was achieved through a variety of methods including two research studies, a systematic review and a critique of a frequently used psychometric measure.